Underground tales, overground lives: mobile work identities through to post-retirement. Issue 1 (2nd January 2021) - Murray, Lesley; Raisborough, Jayne; Monson, Kate
ABSTRACT: Although there has been recent attention given to the subject of mobile work, there has been less focus, within mobility studies, on the work of those who enable movement: the job of the transport worker. This article takes this incarnation of mobile workers as the basis for understanding the ways in which mobile work identities are pulled through into retirement. The article first proposes that transport workers, as movement enablers, have particular identities and are an important and neglected topic of study within mobilities. Second, it suggests that the post-work identities of mobile workers are contingent on their experiences during their working lives and that these are particular to mobile work. The article is evidenced through data gathered during a mobile ethnographic study with two retired London Underground employees. The participants joined the researchers on a walking tour of a disused underground railway station in London, "Hidden London", organized by the London Transport Museum and their experiences and emotional responses were recorded and analysed. Understanding post-work identities through the embodied and spatial experiences of the present, the research sought insights of the past and future: the continuity and fluidity of working identities that permeated through to post-work lives. This article argues that mobile work identities are specific identities that shape a distinct post-retirement identity.